Calcium Ions Aggravate Alzheimer’s Disease Through the Aberrant Activation of Neuronal Networks, Leading to Synaptic and Cognitive Deficits - Guan, Pei-Pei; Cao, Long-Long; Yang, Yi; Wang, Pu (Frontiers in Molecular Neuroscience, 2021)
Alzheimer's disease (AD) is a neurodegenerative disease, which is characterized by the production and deposition of β-amyloid protein (Aβ) and hyperphosphorylated tau, leading to the formation of β-amyloid plaques (APs) and neurofibrillary tangles (NFTs). Since calcium ions (Ca2+) have shown its effects on promoting the formation of APs and NFTs, there is no systematic review on the mechanisms by which Ca2+ effects the development and progression of AD. Therefore, the current review aimed to fill the gaps between Ca2+ elevation and pathogenesis of AD. Specifically, we mainly focus on the molecular mechanisms by which Ca2+ affect the neuronal networks of neuroinflammation, neuronal injury, neurogenesis, neurotoxicity, neuroprotection and autophagy. Furthermore, the roles of Ca2+ transporters located in cell membrane, endoplasmic reticulum (ER), mitochondria and lysosome were respectively addressed to mediate the effects of Ca2+ on activating neuronal networks, which finally contribute to the development and progression of AD. Finally, the drug candidates derived from herbs used as food or seasoning in Chinese daily life were summarized to provide a theoretical basis for improving the clinical treatment of AD.